A method for predicting the initial liquid phase concentration of directional solidification of magnesium-lithium alloy

By establishing a prediction method for directional solidification of magnesium lithium alloys, considering heat transfer and mass transfer and lithium element volatility during standstill heat, the problem of concentration deviation in traditional methods is solved, and the accurate prediction and mechanical properties of magnesium lithium alloy concentration are achieved. Improvement.

CN114334016BActive Publication Date: 2024-12-24LANZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202111249362.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-26
Publication Date
2024-12-24
Estimated Expiration
2041-10-26

AI Technical Summary

Technical Problem

The traditional directional solidification method of magnesium lithium alloy ignores the heat transfer and mass transfer and the volatility of lithium elements when the static heat is stable, causing the concentration of subsequent directional solidification to deviate from the original components, affecting the mechanical properties of the alloy.

Method used

A method for predicting the liquid phase concentration of directional solidification of magnesium lithium alloys was established. Combined with the law of conservation of mass of the reaction system and the volatility of lithium elements, the concentration of the complete liquid phase area after the static heat is stabilized, providing accurate for subsequent directional solidification. Concentration guidance.

Benefits of technology

By considering the heat transfer and mass transfer and lithium element volatility during the static heat stabilization process, the predicted concentration is highly consistent with the actual concentration, which improves the accuracy and mechanical properties of subsequent directional solidification, and is suitable for magnesium lithium alloys and other volatile elements. Alloy system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114334016B_ABST
    Figure CN114334016B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for predicting the concentration of the starting liquid phase of a magnesium-lithium alloy directional solidification. According to the law of conservation of mass of a reaction system, the actual concentration C of a magnesium-lithium alloy sample rod when it is thermally stable at rest is calculated. 0 , TGZM effect and volatilization of lithium element, and establish a prediction model for the melt concentration in the complete liquid zone and the static thermal stabilization time; according to the prediction model, the directional solidification starting liquid phase concentration C near the mushy zone after static thermal stabilization for different times is obtained; the directional solidification starting liquid phase concentration C after static thermal stabilization for different times is used as the actual concentration during directional solidification to carry out qualitative solidification of magnesium-lithium alloy. The prediction method of the present invention simultaneously considers the heat and mass transfer in the static thermal stabilization process and the volatilization of lithium element under different conditions, and predicts the concentration of the complete liquid phase zone before directional solidification, providing inherent and important guidance for subsequent directional solidification.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of directional solidification of magnesium-lithium alloys, and in particular to a method for predicting the concentration of a starting liquid phase of directional solidification of a magnesium-lithium alloy. Background Art

[0002] The density of magnesium-lithium alloy is only 1.30-1.65g / cm 3 , only 1 / 2 of aluminum alloy and 3 / 4 of traditional magnesium alloy, it is the lightest metal structural material to date. As the lightest structural material, magnesium-lithium alloy not only has the characteristics of high specific stiffness, high elastic modulus, good machinability, good plasticity, good impact toughness, good low-temperature toughness, good damping performance, but also has good magnetic shielding and shockproof performance, which can reduce the interference of cosmic rays on electronic instruments and equipment and meet the demand of aviation and aerospace industries for lightweight materials. In 2017, the article "The Lightest New Metal Structural Material-Magnesium-Lithium Alloy" was published in Volume 4, Issue 6 of "World Nonferrous Metals", pointing out that the improvement of the absolute strength of magnesium-lithium alloy is the key factor in improving its application range. Therefore, researchers have conducted a lot of research on improving the strength of magnesium-lithium alloys. At present, there are three most commonly used methods: alloying, heat treatment and plastic deformation. And directional solidification, as a good method for preparing metals, can also be used to improve the mechanical properties of alloys.

[0003] Generally, magnesium alloy directional solidification is mainly carried out by the traditional Bridgman method, and its process principle and characteristics are described in detail in the book "Directional Solidification of Aerospace Materials" published by Science Press in 2015. For magnesium-lithium alloys, "Materials and Design" published an article in Volume 60 in 2017 titled "Effects of composition and growth rate on the microstructure transformation of β-rods / lamellae / α-rods in directionally solidified Mg-Li alloy". The Bridgman directional solidification method was used to characterize the morphology of magnesium-lithium alloys at different lithium contents and withdrawal rates. The results show that different lithium contents and withdrawal rates have a great influence on the microstructure of magnesium-lithium alloys.

[0004] Usually, static thermal stabilization is the first stage of directional solidification, which can obtain a uniform melt concentration for the subsequent directional solidification. During the static thermal stabilization process, a mushy zone is formed between the completely liquid zone and the original cast zone due to the applied temperature gradient. After static thermal stabilization, the melt concentration in the completely liquid zone is generally considered to be equal to the initial composition of the sample. However, some researchers have found that the melt concentration in the completely liquid zone deviates from the initial concentration after thermal stabilization. Further research has found that this phenomenon is related to the temperature gradient zone melting (TGZM) effect, which causes the droplets in the mushy zone to solidify at the cold end and the solid phase to melt at the hot end. Therefore, the droplets in the mushy zone will look like they migrate to a higher temperature position. As the thermal stabilization time increases, more droplets migrate from the mushy zone to the completely liquid zone, so the concentration in the completely liquid zone will change. The change in the concentration in the completely liquid zone will cause the concentration of the subsequent directional solidification to deviate from the original alloy composition, thereby affecting the volume fraction and distribution of the phase in the alloy, and then affecting the mechanical properties of the alloy. The prior art generally assumes that the concentration of subsequent directional solidification is equal to the original alloy composition, without considering the heat and mass transfer during static thermal stability. Therefore, for the subsequent directional solidification samples, if the TGZM effect is not considered, the mechanical properties of the alloy will have a certain deviation (because the actual solidification composition deviates from the original composition). Therefore, considering the heat and mass transfer during static thermal stability (TGZM effect) is of great significance for the subsequent directional solidification.

[0005] In addition, lithium is more volatile in magnesium-lithium alloys. Studies have shown that the loss of lithium will lead to changes in the alloy composition, so the volume fraction of each phase in the magnesium-lithium alloy will change. This will affect its mechanical properties. Therefore, during the thermal stabilization process, the volatilization of lithium in magnesium-lithium alloys should be considered.

[0006] From the above reports on the directional solidification of magnesium-lithium alloys, the following problems can be found: (1) The traditional directional solidification method of magnesium-lithium alloys assumes that the liquid phase concentration is consistent with the initial composition of the alloy during solidification, and ignores the heat and mass transfer during the static thermal stabilization before directional solidification; (2) General directional solidification does not take into account the volatilization of elements during heating; (3) There is no in-depth research on the specific impact of element volatilization. Summary of the invention

[0007] In order to solve the problems existing in the prior art, the present invention provides a method for predicting the concentration of the initial liquid phase of directional solidification of magnesium-lithium alloy, while considering the heat and mass transfer in the static thermal stabilization process and the volatilization of lithium under different conditions, to predict the concentration of the complete liquid phase zone before directional solidification, providing inherent and important guidance for subsequent directional solidification.

[0008] To achieve the above object, the present invention provides the following technical solution: a method for predicting the concentration of the starting liquid phase of directional solidification of magnesium-lithium alloy, the specific steps are:

[0009] S1 According to the law of conservation of mass of the reaction system, the actual sample concentration C0, TGZM effect and volatilization of lithium element of the magnesium-lithium alloy sample rod during static thermal stability are combined to establish a prediction model of melt concentration and static thermal stability time in the complete liquid zone;

[0010] S2 obtains the initial liquid phase concentration C of directional solidification near the mushy zone after standing for different time for thermal stability according to the prediction model;

[0011] S3 uses the obtained directional solidification starting liquid phase concentration C as the actual concentration during directional solidification to carry out qualitative solidification of the magnesium-lithium alloy.

[0012] Furthermore, in step S1, the magnesium-lithium alloy sample rod is a Mg-7.3wt%Li alloy, and the Mg-7.3wt%Li alloy is statically heat stabilized by a Bridgman directional solidification method.

[0013] Furthermore, in step S1, according to the law of conservation of mass of the reaction system, the sum of the total dissolved mass of the solid phase in the paste zone, the total dissolved mass of the complete liquid zone, the total dissolved mass of the liquid phase in the paste zone and the volatilization amount of the lithium element is equal to the mass of the lithium element in the paste zone and the complete liquid phase zone after the entire sample rod is allowed to stand and thermally stabilize.

[0014] Further, in step S1, the relationship between the mass of lithium element after static thermal stabilization and the mass of lithium element before static thermal stabilization is expressed as:

[0015]

[0016] Among them, f α is the volume fraction of liquid phase in the mushy zone, L α is the length of the mushy zone, C ɑ is the concentration at the liquidus, L g is the volatilization length of the sample, C g is the volatile concentration, L is the total length of the complete liquid phase and the mushy zone; C L (α) is the liquid melt concentration in the mushy zone; χ α is the temperature gradient direction in the mushy zone T E and T L The length between them; C0 is the actual concentration of the complete liquid phase zone near the mushy zone; C is the starting liquid phase concentration of directional solidification near the mushy zone after standing and thermal stabilization.

[0017] Furthermore, in step S1, C L (α) is the liquid melt concentration in the mushy zone, which is a function of the distance between the eutectic temperature line and the liquidus line, specifically:

[0018]

[0019] Among them, CE is the eutectic temperature T E The melt concentration under the condition of G is the temperature gradient, is the liquidus slope C ɑ is the concentration at the liquidus.

[0020] Furthermore, in step S1, the volatilization concentration of the solute is:

[0021] C g =3.5L g (9).

[0022] Furthermore, in step S1, when predicting the liquid phase concentration C at the start of directional solidification after a short period of static thermal stabilization, the prediction model takes into account the volatilization of lithium elements.

[0023] Furthermore, in step S1, the prediction model is:

[0024]

[0025] in,

[0026]

[0027]

[0028] Where G is the parameter temperature gradient, is the liquidus slope C ɑ is the concentration at the liquidus, C E is the eutectic temperature T E The melt concentration under this condition; D is the mass of lithium element considering the volatilization of lithium.

[0029] Furthermore, in step S1, when predicting the liquid phase concentration C at the start of directional solidification after long-term thermal stabilization, the prediction model does not consider the volatilization of lithium elements.

[0030] Furthermore, in step S1, the prediction model is:

[0031]

[0032] in,

[0033]

[0034] Where G is the parameter temperature gradient, is the liquidus slope C ɑ is the concentration at the liquidus, C E is the eutectic temperature T E The melt concentration is below.

[0035] Compared with the prior art, the present invention has at least the following beneficial effects:

[0036] The present invention provides a method for predicting the concentration of the initial liquid phase of a directional solidification magnesium-lithium alloy. The method aims to predict the concentration of the complete liquid phase of the directional solidification Mg-Li alloy after different static thermal stabilization times. The method establishes a prediction model to predict the concentration of the complete liquid phase of the Mg-Li alloy after different static thermal stabilization times. The predicted concentration is used as the concentration of the complete liquid phase of the directional solidification Mg-Li alloy to prepare for subsequent directional solidification.

[0037] The prediction method of the present invention has a simple model calculation when lithium volatilization is considered. In addition to the magnesium-lithium alloy mentioned in the present invention, it can also provide theoretical guidance for the prediction of melt concentration after short-term static thermal stabilization when other alloy systems contain volatile elements, and the theoretical prediction value is highly consistent with the actual concentration when the static thermal stabilization time is short.

[0038] The prediction method of the present invention has a wider application range when lithium volatilization is not considered. It can be applied to magnesium-lithium alloys (and other alloy systems containing volatile elements) that are thermally stable for a long time. When the thermal stability time is long, the theoretical prediction value is basically consistent with the actual concentration. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 Microstructure in the as-cast state;

[0040] Figure 2 The structure of the paste area after different standing thermal stabilization times, including (a) the structure of the paste area after different standing thermal stabilization times of 1 min, (b) the structure of the paste area after different standing thermal stabilization times of 5 min, (c) the structure of the paste area after different standing thermal stabilization times of 30 min, and (d) the structure of the paste area after different standing thermal stabilization times of 120 min;

[0041] Figure 3 Relationship between the fixation range and different parts of the sample during thermal stabilization: (a) Schematic diagram of the relevant part of the magnesium-lithium binary phase diagram; (b) the formation of different regions in the sample after thermal stabilization;

[0042] Figure 4 Schematic diagram of lithium volatilization during static thermal stability;

[0043] Figure 5 Comparison between theoretical predictions and experimental measurements obtained in this invention. DETAILED DESCRIPTION

[0044] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.

[0045] For eutectic Mg-Li alloys, directional solidification is a feasible way to improve mechanical properties. Before the start of directional solidification, a static thermal stabilization process is usually required to obtain a uniform melt concentration. During this process, a mushy area will be formed in the complete liquid phase area and the original solid phase area. The composition in the liquid phase is the composition of the directionally solidified sample. In the eutectic Mg-Li alloy, with the increase of the static thermal stabilization time, the composition in the liquid phase will also change, that is to say, the concentration of the directionally solidified magnesium-lithium alloy obtained after static thermal stabilization for different times is also different. In order to quantitatively predict the composition in the liquid phase after static thermal stabilization, the present invention provides a method for predicting the concentration of the initial liquid phase of the directional solidification of magnesium-lithium alloys. Considering the mass transfer phenomenon of the static thermal stabilization process and the volatilization of lithium, the concentration of the complete liquid phase area of ​​the sample after static thermal stabilization for different times is predicted, providing theoretical support for subsequent directional solidification:

[0046] The specific technical solutions adopted are as follows:

[0047] Step 1: Heat stabilize the Mg-7.3wt%Li alloy by Bridgman directional solidification method.

[0048] Step 2: Cut the sample longitudinally, polish it and analyze the microstructure of the longitudinal section of the sample rod by scanning electron microscopy.

[0049] Step 3: Measure the length L of the mushy area of ​​the sample rod after different static thermal stabilization times α , the liquid volume fraction in the mushy zone f α , and the concentration of the complete liquid phase area near the paste area, which is the actual concentration C0 of the complete liquid phase area of ​​the sample rod.

[0050] Step 4: Based on the actual concentration C0 of the sample and the volatilization of TGZM and lithium, a model is established for analysis and calculation to obtain the starting liquid phase concentration C of directional solidification near the mushy zone after static thermal stabilization.

[0051] Step 5: Compare the predicted starting liquid phase concentration C of directional solidification with the experimentally measured concentration of the complete liquid phase region to verify the reliability of the concentration model of the complete liquid phase region near the mushy region after static thermal stabilization considering the volatilization of elements, so as to use the starting liquid phase concentration C of directional solidification to provide theoretical guidance for subsequent directional solidification.

[0052] Step 6: Use the initial liquid phase concentration C of directional solidification after standing for different periods of time for thermal stabilization as the actual concentration during directional solidification to perform qualitative solidification of the magnesium-lithium alloy.

[0053] The principle of the present invention is as follows:

[0054] The present invention takes a static thermally stable Mg-7.3wt%Li alloy sample as an example to verify the relationship between different static thermal stabilization times and the concentration of the complete liquid phase region near the mushy region.

[0055] The cast microstructure of the eutectic Mg-Li alloy is that the white phase is the α-Mg phase and the gray phase is the eutectic (α-Mg+β-Li). In addition, it can be seen that the α-Mg phase has a dendrite-like morphology, such as Figure 1 shown.

[0056] Then, the Mg-Li rod is placed in a high-purity BN crucible and the upper end is heated to a preset temperature, i.e., 650-700°C, and the lower end of the Mg-Li rod is placed in the Ga-In liquid. Under the action of this temperature gradient, the upper end of the Mg-Li melts and becomes a completely liquid phase area, while the lower end is the original cast structure. In the middle of these two areas, a mushy area will be formed, such as Figure 2 As shown in Figure 2, a mushy region is formed between the unmelted solid region and the completely liquid region. In addition, liquid channels can be observed in the mushy region. It is worth noting that when the static thermal stabilization time is 1 min ( Figure 2 (a)) and 5min( Figure 2 (b)), the channels in the paste zone are clear. When the static thermal stability time is 30 minutes, Figure 2 As shown in (c), fewer channels can be observed. When the thermal stabilization time is increased to 2 h ( Figure 2 (d)), the channel disappears, and only the α-Mg phase can be observed in this area. In addition, the volume fraction of the liquid phase in the mushy zone decreases with the increase of the thermal stabilization time. It can be seen that after different static thermal stabilization times (1min, 5min, 30min, 120min), the length of the mushy zone and the volume fraction of the liquid phase in the mushy zone have changed. This is caused by the temperature gradient zone melting (TGZM) effect, which causes heat and mass transfer between the mushy zone and the completely liquid zone. Therefore, the melt concentration in the completely liquid phase zone will change, which will affect the subsequent directional solidification. At the same time, Figure 2 The eutectic interface (T E ) morphology evolution, it can be seen that the interface did not change during the thermal stabilization process, confirming that there was no mass transfer between the mushy region and the non-molten solid region during the thermal stabilization process.

[0057] The reason why the mushy zone is formed during the thermal stabilization process can be Figure 3 For eutectic Mg-Li alloy, the solidification path is: when the temperature reaches the liquidus temperature, T L =595℃:L→L+α-Mg; when the temperature reaches the eutectic reaction temperature T E=588℃: L→α-Mg+β-Li (eutectic reaction, α is solid phase, L is liquid phase, L+α is pasty region). L , T E Corresponding to the liquidus and eutectic temperature respectively. When a temperature gradient is applied to the alloy, a mushy zone is formed between the completely liquid zone and the non-melting solid zone. From the bottom to the top of the mushy zone, a temperature gradient with T E and T L Two corresponding interfaces.

[0058] In addition, the volatilization of lithium can be regarded as the diffusion of lithium atoms from the inside of the sample to the surface, oxidation in the air, or sublimation in a vacuum or inert gas environment. The particularity of Mg-Li alloy is that lithium is a volatile element, so it is necessary to discuss the loss of lithium, such as Figure 4 As shown. In the present invention, the volatilization of lithium in the Mg-Li alloy will inevitably affect the diffusion of the solute, and the temperature of the complete liquid phase region and the paste region in the present invention is higher than the temperature of the original solid phase region, so a large amount of lithium atoms will volatilize and enter during the thermal stabilization process. Therefore, during the thermal stabilization process of the Mg-Li alloy, the volatilization of lithium should also be taken into consideration.

[0059] According to the above, an analytical model was established to predict the melt concentration in the completely liquid region after different thermal stabilization times. In this model, the TGZM effect and the volatilization of lithium during the static thermal stabilization process were considered simultaneously.

[0060] The model is established as follows:

[0061] According to step 4, during the static thermal stabilization process, except for the volatilization of lithium, there is no mass transfer between different parts of the sample and the outside of the sample, so the law of conservation of mass should be reasonable within the system. On this basis, the initial liquid phase concentration C of directional solidification can be associated with the liquid migration in the eutectic system and the changes in the volume fractions of each phase in the mushy zone.

[0062] This model is based on the following assumptions:

[0063] (1) The total length of the sample is L0, and the total length of the complete liquid phase and the mushy region is L.

[0064] (2) The liquidus and solidus of α-Mg and β-Li phases are both straight lines.

[0065] (3) The volatilization of lithium is much higher than that of magnesium, so the volatilization of magnesium can be ignored;

[0066] 4.1 In order to establish the relationship between concentration and static thermal stabilization time, it is assumed that the mass of lithium in the system does not change. According to the law of mass conservation in the system, the mass of lithium after static thermal stabilization is the same as that before static thermal stabilization. Therefore, the relationship between the mass of lithium after static thermal stabilization and the mass of lithium before static thermal stabilization can be expressed as:

[0067]

[0068] Among them, f α is the volume fraction of liquid phase in the mushy zone, L α is the length of the mushy zone, C ɑ is the concentration at the liquidus, L g is the volatilization length of the sample, C g is the volatile concentration, L is the total length of the complete liquid phase and the mushy zone, C L (α) is the liquid melt concentration in the mushy zone, χ α is the temperature gradient direction in the mushy zone T E and T L C0 is the actual concentration of the complete liquid phase near the mushy zone, and C is the starting liquid phase concentration of directional solidification near the mushy zone after standing and thermal stabilization.

[0069] Therefore, the first term on the left side of formula (1) is the total solubility of the solid α phase in the paste region. The second term is the total solubility of the complete liquid region. The third term is the total solubility of the liquid phase in the paste region. The fourth term in formula (1) is the volatilization amount of the solute. Therefore, the sum of the four terms on the left side is the mass of lithium in the paste region and the complete liquid region after standing and thermally stabilizing. The right side of formula (1) is the mass of lithium in the paste region and the complete liquid region after the entire sample is standing and thermally stabilizing. Both sides are equal.

[0070] Furthermore, in formula (1), the first term on the left side of formula (1) can be calculated directly, and C in the second term is the starting liquid concentration of directional solidification to be calculated, (LL α ) is known; one term on the right can also be calculated directly.

[0071] 4.2 Calculate the total solute in the liquid phase of the third mushy region, C L (α) is a function of the distance between the eutectic temperature line and the liquidus line (i.e., C L (α) is a function of the length of the mushy zone), the relationship is as follows:

[0072]

[0073] Among them, C E is the eutectic temperature T E The melt concentration under the condition of G is the temperature gradient, is the liquidus slope C ɑis the concentration at the liquidus. Substituting (2) into the third term in (1) yields:

[0074]

[0075] Thus, the calculation of the third term is completed, and only the fourth term in formula (1), i.e., the volatilization of lithium element, remains unknown.

[0076] 4.3 In order to calculate the volatilization of lithium, the volatilization formula of lithium in a closed system is introduced:

[0077]

[0078] Where C0 is the actual concentration of the complete liquid phase near the mushy zone, the initial concentration of the alloy is Mg-7.3Li, C ∞ is the concentration in the closed system of the alloy preparation environment. M is a constant. Then, we substitute and integrate to obtain the concentration of the alloy volatilization:

[0079] C g =C ∞ (1-e -Mt )+7.3e -Mt (5)

[0080] Furthermore, the length of the alloy after volatilization is calculated by introducing the following formula:

[0081] L(t)=L0(1-e -Mt ) (6)

[0082] Where L0 is the initial length of the alloy, t is the thermal stability time, and M is a constant.

[0083] The change in the total length of the sample rod can be given by formula (6). The concentration and length of the volatilization are given by formulas (5) and (6) respectively. The volatilization length can be directly measured, so it is a known number. The concentration of the volatilization needs to be calculated by the constant M, and M is unknown. However, according to formulas (5) and (6) and the diffusion relationship of atoms in the alloy, the relationship between the concentration of the volatilization and the length is given by the following formula:

[0084]

[0085] Where ΔC and ΔL are the volatile concentration and length respectively, V Mg and V Li is the atomic volume, V Li =21.5×10-24cm3, V Mg =25.0×10-24cm3, substituting into formula (8), we get:

[0086] ΔC=3.5ΔL (8)

[0087] According to formulas (7) and (8), we can get a simple relationship between the volatilization length and the concentration:

[0088] C g =3.5L g (9)

[0089] Thus, the concentration of the volatilizer in the alloy can be represented by the length of a known amount of volatilization.

[0090] At this point, all calculations in formula (1) are completed, and only the initial liquid concentration C of directional solidification is unknown. Substituting the already calculated formulas (3) (9) into formula (1), when considering lithium volatilization, the calculation results can be obtained as follows:

[0091]

[0092] in,

[0093]

[0094]

[0095] Finally, formula (10) is used to predict the liquid phase concentration. Formula (11), formula (12) and formula (13) are the specific parameters of A, B, and D in formula (10), where D in formula (13) is the mass of lithium element considering lithium volatilization.

[0096] If the volatilization of lithium is not considered, the calculation result can be obtained as follows:

[0097]

[0098] in,

[0099]

[0100] Where G is the parameter temperature gradient, χ α is the temperature gradient direction in the mushy zone T E and T L The length between α is the length of the mushy zone, is the liquidus slope; C ɑ is the concentration at the liquidus, f α is the volume fraction of liquid phase in the mushy region, Lg is the volatilization length which can be directly measured, C E is a known quantity; L is the total length of the complete liquid phase and the mushy zone, and C0 is the actual concentration of the sample. Thus, the theoretical model can be calculated and verified.

[0101] Substituting into the final theoretical prediction value, we can get Figure 5 As shown. The theoretical prediction value includes two results. First, theoretical prediction 1 takes into account the volatilization of lithium elements, that is, the result of its calculation is the result of the final formula (10). Second, theoretical prediction value 2 does not take into account the volatilization of lithium elements, that is, the result of its calculation is the result of removing the D term on the right side of the numerator in the final formula (10) (i.e., formula (14)).

[0102] Figure 5 At the same time, a comparison between the theoretical prediction of the present invention and the experimental measurement is given. It can be seen from the figure that the theoretical prediction is close to the experimental measurement, which proves the effectiveness of the model in this paper. Theoretical predictions 1 and 2 respectively give the conditions for considering or not considering the volatilization of lithium elements. When the volatilization of lithium elements is considered (theoretical prediction 1), it can be obtained that when the thermal stabilization time is short, that is, 1 minute, the current theoretical prediction is closer to the experimental measurement. Therefore, for the static thermal stability considering the volatilization of lithium elements, the theoretical prediction 1 can be used to predict the melt concentration after static thermal stabilization, providing guidance for subsequent directional solidification. For example, in this experiment, when the static thermal stabilization time is 1 minute, the actual melt concentration is 7.3wt.%, and the theoretical prediction value is 7.325wt.%. The two are relatively close, so it can be used to predict the melt concentration after short-term static thermal stabilization when other alloy systems contain volatile elements.

[0103] When the volatilization of lithium is not considered, the theoretical prediction 2 is close to the experimental measurement when the thermal stability time is 5min, 30min and 120min respectively. The reason is as follows: According to formulas (8), (9), (10) and (13), L g As the thermal stability time increases, C g With L g The value of D in formula (12) increases with the increase of the static thermal stabilization time. However, in fact, the gas pressure of the system gradually reaches the saturated vapor pressure. Therefore, the mass of lithium diffused into the argon atmosphere decreases with the increase of the thermal stabilization time. Therefore, for C g The theoretical prediction will be larger than the experimental measurement. Therefore, the theoretical prediction value of D in Eq will be larger than the experimental measurement value. It can be seen that when the static thermal stabilization time is 120min, the actual melt concentration is 7.28wt.%, and the theoretical prediction value is 7.8wt.%, which is close to each other. Therefore, it can be used to predict the melt concentration after long-term static thermal stabilization when other alloy systems do not contain volatile elements.

[0104] The actual concentration of the directional solidification of the magnesium-lithium alloy has a great relationship with its mechanical properties. Different components and different phase distributions will result in different mechanical properties. Therefore, the concentration of the directional solidified magnesium-lithium alloy obtained after static thermal stabilization is also different. The model of the present invention can predict the initial liquid phase concentration C of the directional solidification after static thermal stabilization at different times. Through subsequent mechanical property tests of the directional solidification samples, the relationship between the magnesium-lithium alloys of different concentrations and their mechanical properties can be established. After the present invention is statically thermally stabilized for 4 different times, four different complete liquid phase concentrations are obtained, which is equivalent to 4 different directional solidification samples. The mechanical properties of the subsequent directional solidification of the 4 samples (assuming that the directional solidification parameters of the four samples are consistent) will be different, and the actual concentrations of the four samples are highly consistent with the concentration of the complete liquid phase predicted by the present invention. It can be seen that the difference in mechanical properties of the 4 directional solidification samples is caused by the concentration of the complete liquid phase.

[0105] In summary, the predicted complete liquid phase concentration can be used to provide theoretical guidance for the improvement of the mechanical properties of subsequent directional solidification magnesium-lithium alloys, that is, a one-to-one correspondence between the complete liquid phase concentration and the mechanical properties of subsequent directional solidification samples can be obtained, thereby achieving the purpose of controlling the microstructure and mechanical properties of the Mg-Li alloy after directional solidification. Therefore, by predicting the initial liquid phase concentration C of directional solidification, the mechanical properties of subsequent directional solidification magnesium-lithium alloys can be analyzed.

Claims

1. A method for predicting the concentration of the starting liquid phase of a magnesium-lithium alloy during directional solidification, characterized in that: The specific steps are: S1 According to the law of conservation of mass of the reaction system, the actual concentration of the sample of the magnesium-lithium alloy sample rod when it is static and thermally stable C 0. Combining the TGZM effect with the volatilization of lithium, a prediction model for the melt concentration and static thermal stability time in the complete liquid zone is established; S2 According to the prediction model, the concentration of the starting liquid phase of directional solidification near the mushy zone after standing for different time for thermal stability is obtained. C ; S3 will obtain the concentration of the starting liquid phase of directional solidification C Qualitative solidification of magnesium-lithium alloy as the actual concentration during directional solidification; In step S1, the relationship between the mass of lithium element after standing and thermally stabilizing and the mass of lithium element before standing and thermally stabilizing is expressed as: in, f α is the volume fraction of liquid phase in the mushy zone, L α is the length of the mushy zone, C ɑ is the concentration at the liquidus, L g is the volatilization length of the sample, C g is the volatile concentration, L is the total length of the completely liquid and mushy regions; C L (α) is the liquid melt concentration in the mushy zone; α is the temperature gradient direction in the mushy zone T E and T L The length between C 0 is the actual concentration in the completely liquid phase region near the mushy region; C is the concentration of the starting liquid phase of directional solidification near the mushy zone after standing and thermal stabilization; In step S1, after a short period of static heat stabilization, the liquid phase concentration at the start of directional solidification is C When predicting, the prediction model takes into account the volatilization of lithium elements; In step S1, the prediction model is: in, ; ; ; G is the parameter temperature gradient, Liquidus slope C ɑ is the concentration at the liquidus, C E is the eutectic temperature T E Melt concentration under D The mass of lithium element to take into account lithium volatilization.

2. The method for predicting the concentration of the starting liquid phase of directional solidification of a magnesium-lithium alloy according to claim 1, characterized in that: In step S1, the magnesium-lithium alloy sample rod is a Mg-7.3wt%Li alloy, and the Mg-7.3wt%Li alloy is statically heat-stabilized by a Bridgman directional solidification method.

3. The method for predicting the concentration of the starting liquid phase of directional solidification of a magnesium-lithium alloy according to claim 1, characterized in that: In step S1, according to the law of conservation of mass of the reaction system, the sum of the total dissolved mass of the solid phase in the paste region, the total dissolved mass of the complete liquid region, the total dissolved mass of the liquid phase in the paste region and the volatilization amount of lithium element is equal to the mass of lithium element in the paste region and the complete liquid phase region after the entire sample rod is allowed to stand and thermally stabilize.

4. The method for predicting the concentration of the starting liquid phase of directional solidification of a magnesium-lithium alloy according to claim 1, characterized in that: In step S1, C L (α) is the liquid melt concentration in the mushy zone, which is a function of the distance between the eutectic temperature line and the liquidus line, specifically: in, C E is the eutectic temperature T E The melt concentration under G is the temperature gradient, Liquidus slope C ɑ is the concentration at the liquidus.

5. The method for predicting the concentration of the starting liquid phase of directional solidification of a magnesium-lithium alloy according to claim 1, characterized in that: In step S1, the volatilization concentration of the solute is: in, L g is the volatilization length of the sample.

6. The method for predicting the concentration of the starting liquid phase of directional solidification of a magnesium-lithium alloy according to claim 1, characterized in that: In step S1, after long-term thermal stabilization, the liquid phase concentration at the start of directional solidification is C When making predictions, the prediction model does not take into account the volatilization of lithium.

7. The method for predicting the concentration of the starting liquid phase of directional solidification of a magnesium-lithium alloy according to claim 6, characterized in that: In step S1, the prediction model is: in, ; ; G is the parameter temperature gradient, Liquidus slope C ɑ is the concentration at the liquidus, C E is the eutectic temperature T E The melt concentration is below.